Desempenho acadêmico e motivação esportiva dos alunos do Instituto Federal de Mato Grosso - Marques, Fernanda Gabriella Pedroso (2019)
The adoption of a more active lifestyle, through the practice of regular physical activity, has shown to be an effective factor in preventing diseases and promoting both physical and mental health, therefore, it should be stimulated throughout life. Among the several variables that can influence sports practice and academic performance, motivational aspects stand out in the literature, once they are related with the adherence and maintenance of the practice of any type of activity. The aim of the study was to verify the motivational characteristics and academic performance of IFMT students, considering the participation in the JIFMT. The Federal Institutes Games (JIF) are carried out nationwide and organized in three phases: the first stage is state (JIFMT) and takes place at the institution itself; the classifieds go to the regional step; finally the champions compete at the national stage (JIF). The sample consisted of 93 JIFMT participants (17.35 ± 1.32 years old) and 65 non-participating students (16.57 ± 1.27 years old) of both sexes. In the first part of the research, the subjects answered a sociodemographic questionnaire and the sports motivation questionnaire (SMS-28). In the second part of the research, the academic records of all students were collected. There were no significant differences in academic performance in function to participation in JIFMT. The JIFMT participants are significantly more sportively motivated than non-participants. The participating students of the JIFMT were related to consider themselves physically active, preferred leisure activity and the beginning of sports practice. Finally, the participating students in the JIFMT had a bigger engagement/pretense in physical practices